Microbial mechanisms of using feruloyl esterase-producing Lactobacillus plantarum A1 and grape pomace to improve fermentation quality and mitigate ruminal methane emission of ensiled alfalfa for cleaner animal production. (15th April 2022) - Zhang, Xia; Ke, Wencan; Ding, Zitong; Xu, Dongmei; Wang, Musen; Chen, Menyan; Guo, Xusheng
Abstract: This study was conducted to investigate the influence of feruloyl esterase-producing Lactobacillus plantarum A1 (Lp A1) and grape pomace (GP) alone, or in combination (LG) on ensiling characteristics and bacterial community, in vitro ruminal fermentation, methane (CH4 ) emission, and the microbiota of ensiled alfalfa. Alfalfa at 42% dry matter (DM) was treated in a 2 × 2 factorial design: with the application of Lp A1 at 0 (control) or 1 × 10 6  cfu/g of fresh forage, and GP at 0 or 5% of fresh forage. After 60 d of ensiling, a decrease in nonprotein nitrogen (NPN) was observed in GP treated silage. Lp A1 inoculated silage had a lower fiber content than silages without Lp A1. The lowest NPN was found in silage treated with LG, and an obvious increase in the relative abundance of Lactobacillus paracasei was detected in silages treated with Lp A1 and LG, respectively. In vitro ruminal experiments indicated that, although the application of GP deceased ruminal total gas, CH4 production, nitrogen degradation and the number of methanogenic archaea in alfalfa silage, it also reduced silage DM digestibility. In contrast, inoculation with Lp A1 not only increased DM digestibility and populations of ruminal Ruminococcus flavefaciens and fungi, but also improved ruminal total gas and CH4 production. As expected, LG treatment decreased alfalfa silage ruminal total gas and CH4 production relative to Lp A1 treatment alone, and increased silage DM digestibility compared with GP treated silage. In conclusion, the application of LG before ensiling alfalfa, balanced silage proteolysis, feed digestibility, and CH4 emission, and could be a promising strategy for using food industry by-products to produce a nutritional and environmentally-friendly legume silage that will mitigate N and greenhouse gas emissions from ruminants. Highlights: Inoculation of Lp A1 decreased silage fiber content and improved DM digestibility. Application of Lp A1 or Lp A1+GP increased abundance of Lactobacillus in silage. GP addition lowered silage ruminal Methanogenic archaea, DM digestibility in vitro . Addition of GP in silage inhibited in vitro total gas and CH4 emission. Addition of Lp A1+GP in silage balanced CH4 emission and feed digestion.